Investigation of intra-annual glacier velocity and seasonality of Axel Heiberg Island - Samo, Lauren; van Wychen, Wesley; Wendleder, Anna (2021)
The Canadian Arctic Archipelago (CAA) is undergoing rapid atmospheric warming at rates that are twice that of the global average and greater than at any other time in the past four millennia. Longer and more intense melt seasons, modifications in glacier motion, and persistent glacier mass loss are all changes in glacier behavior being experienced due to the increase in air temperature. To understand the impacts of this warming trend, this study will investigate seasonality in ice motion with a focus on two glaciers; Thompson and White Glacier on Axel Heiberg Island, one of which contains the longest in situ mass balance record in the Canadian Arctic. This research builds on previous research by creating a dense time series of glacier motion over a ~10 year period (winter 2008/2009 to winter 2019/2020), thus improving upon spatial and temporal resolution of earlier work. The main objective is to quantify seasonal changes in glacier dynamics within a year using the GAMMA Remote Sensing Software to derive surface velocity from SAR imagery (including RadarSat-2, Terra-SAR-X and Sentinel-1 data). These velocities will help quantify seasonality and determine links between changes in sea ice conditions and summer melt and are important to better characterize differing velocity regimes in the CAA.